Credit spreads, business conditions, and expected corporate bond returns - Hai Lin; Xinyuan Tao; Junbo Wang; Chunchi Wu (Journal of Risk and Financial Management, 2020)
Using an aggregate credit spread index, we find that it has substantial predictive power for corporate bond returns over short and long horizons. The return predictability is economically and statistically significant and robust to various controls. The credit spread index and its components have more predictive power for bond returns than conventional default and term spreads. When decomposing the credit spread index into investment- and speculative-grade components, the latter has more predictive power for future bond returns. The source of the index's predictive power is from its ability to forecast future economic conditions.
Keywords: 330; corporate bonds; credit spreads; default risk; economic conditions; return predictability